Peran Guru Pendidikan Agama Islam dalam Membina Kecerdasan Spiritual Siswa di SMAN 1 Adiluwih - Putri, Helen Oktavia; Aziz Q, Ikhwan; Wijaya, Adi (Attractive : Innovative Education Journal, 2024)
The formulation of the problem in this research is: What is the role of PAI teachers in developing spiritual intelligence in students? Meanwhile, the aim of the research is to determine the role of PAI teachers in fostering spiritual intelligence in students. This qualitative research was conducted at SMAN 1 Adiluwih. Data collection techniques consist of interview, observation and documentation methods. Data sources consist of two primary and secondary data sources. Meanwhile, the validity of the data uses triangulation. Based on the research results, it can be concluded that the role of Islamic Religious Education teachers in developing students' spiritual intelligence at SMAN 1 Adiluwih consists of: First, the role of teachers as educators, namely getting students to respect their teachers, getting used to memorizing short letters, memorizing verses from the Koran, and holding prayers. congregation. Second, the role of the teacher as a guide is to always provide positive direction, provide guidance by communicating well, knowing the desires and character of students, not discriminating between students, providing good examples, getting used to discipline, and equalizing students. Third, the teacher's role as a motivator is to provide encouragement to always study diligently, provide positive direction, provide enthusiasm for learning, and provide appreciation in the form of grades, participate in learning activities, provide motivation through stories of success, and provide warnings to students. The novelty in this research is that this research uses three role indicators, namely the role of the teacher as an educator, the role of the teacher as a guide and the role of the teacher as a motivator, which so far have not been found in scientific work as research indicators, especially in terms of developing students' spiritual intelligence. Keywords: Islamic Religious Education Teachers, Spiritual Intelligence, Role of Islamic Religious Education